Palaeomagnetism of Precambrian igneous rocks in Australia and East Antarctica: implications for the pre-Pangea supercontinents and supercontinent cycle - Liu, Yebo (Curtin University, 2019)
This thesis presents a series of new, high-quality palaeomagnetic data from Precambrian igneous rocks in Western Australia, South Australia and East Antarctica. The ages of the corresponding new palaeomagnetic poles range from late Archaean to late Mesoproterozoic. The new data improve significantly the Australian and East Antarctic palaeomagnetic database and shed lights on the tectonic evolution of Australia and global palaeogeographic reconstructions.